Compositional Controls on the Distribution of Brine in Europa's Ice Shell. Issue 9 (14th September 2022) - Wolfenbarger, N. S.; Fox‐Powell, M. G.; Buffo, J. J.; Soderlund, K. M.; Blankenship, D. D.
Abstract: The composition of impurities in ice controls the stability of liquid water and thus the distribution of potential aqueous habitats. We present a framework for modeling the brine volume fraction in impure water ice as a function of temperature and bulk ice salinity, inspired by models originally developed for sea ice. We applied this framework to examine the distribution of brine within the thermally conductive layer of Europa's ice shell, considering binary (NaCl and MgSO4 ) and multi‐ion "analog" (Cl‐dominated and SO4 ‐dominated) endmember impurity compositions. We found the vertical extent of brine in a conductive ice layer, expressed as a fraction of the total layer thickness, to be <12% for NaCl, <2% for MgSO4, and <18% for both the analog endmember impurity compositions, suggesting that the depth where brine is stable in an ice shell is more sensitive to composition when only two ionic species are present. For the same temperature and bulk ice salinity, the brine volume fraction is higher in a Cl‐dominated ice shell than a SO4 ‐dominated ice shell. Pressure, governed by the ice thickness, was found to have only a minor effect on the vertical extent of brine within an ice shell, relative to temperature and bulk ice salinity. The minimum stable bulk ice shell salinity formed through freezing of an ocean was found to be insensitive to composition and ultimately governed by the magnitude of the assumed percolation threshold. Plain Language Summary: When ice forms from salt water, salt is excluded from the ice causing the remaining liquid water to become more saline, forming brine. We developed a method to build models that estimate how much brine exists in ice at a certain temperature for a certain amount of salt. Because water is a necessary ingredient for life, places where brine exists in ice represent potential habitats. We applied our method to the ice shell of Jupiter's moon Europa, assuming the ice shell formed from an ocean. Two possible oceans made up of different types of dissolved salts were considered. We found that the depth where brine is stable in an ice shell is more sensitive to the type of salt when two ions are present than when four ions are present. When the salt is made mostly of chloride, a larger volume of brine exists than when the salt is made up mostly of sulfate. The thickness of the ice shell did not affect the percentage of the ice layer where brine existed as much as temperature or the amount of salt did. The type of salt in the ocean did not affect how much salt was retained in the ice. Key Points: The brine volume fraction of impure water ice can be represented as a function of temperature and bulk ice salinity For the same temperature and bulk salinity, the brine volume fraction in a Cl‐dominated ice shell is higher than a SO4 ‐dominated ice shell The magnitude of the percolation threshold governs the minimum fraction of salt entrained in ice formed through freezing of an ocean